1995
DOI: 10.1046/j.1537-2995.1995.35795357884.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of polymerase chain reaction and radioimmunoprecipitation assay in the confirmation of human T‐lymphotropic virus infection in French blood donors

Abstract: In the study of a population in which 97 percent of HTLV infections are due to HTLV-I, these data support the three-protein criteria (rgp21, p19, and p24) for a positive blot reading. No HTLV infection was observed when rgp21 did not react. Consequently, p19 and/or p24 band patterns represent false reactivity and do not require PCR or RIPA confirmation. To discriminate between false- and true-positive results in the absence of MTA-1 or K55 reactivity, PCR and/or RIPA is required only when rgp21 reactivity is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This indicates that a certain percentage of the HTLV-1-infected individuals did not present any MTA-1 peptide reactivity, as reported in a few studies (6,15,21,24,74). Furthermore, our study also indicates that, at least in Central Africa, the presence of HGIP is not associated with an infection by HTLV-3 or HTLV-4.…”
Section: Discussionsupporting
confidence: 83%
“…This indicates that a certain percentage of the HTLV-1-infected individuals did not present any MTA-1 peptide reactivity, as reported in a few studies (6,15,21,24,74). Furthermore, our study also indicates that, at least in Central Africa, the presence of HGIP is not associated with an infection by HTLV-3 or HTLV-4.…”
Section: Discussionsupporting
confidence: 83%
“…Also in our study, it was apparent that the rgp21 was the most sensitive for detection of antibodies in HTLV‐II‐infected individuals showing indeterminate reactivity in WB and/or INNO‐LIA (Table 3). The high sensitivity of rgp21 has also been confirmed in a French study, in which no HTLV infection was observed, when rgp21 did not react 26 . Both Murex and Ortho ELISAs contain rgp21 and thereby have the potential of being highly sensitive also during early HTLV infection.…”
Section: Discussionmentioning
confidence: 65%
“…PCR methods (in‐house methods as well as commercially available tests) have been useful to discriminate between HTLV‐I and HTLV‐II infections and resolve infection status of individuals with an indeterminate WB 5,6,12,15,22,26‐30 . Some studies have indicated that the sensitivity for detection of HTLV‐II infection by PCR is lower than that of the serologic methods, 28,30 whereas other studies have indicated that the prevalence of HTLV infection is underestimated by serologic methods in comparison with PCR 6,31,32 …”
mentioning
confidence: 99%
“…This is consistent with previous studies that found that samples classed as indeterminate only occasionally tested positive by polymerase chain reaction. 18 24 25 False positive results with the enzyme linked immunosorbent assay were found in 1 out of 400 donors, giving an overall specificity of 99.8%. This is similar to findings in Holland 18…”
Section: Discussionmentioning
confidence: 99%